Implementasi Nilai Nilai Kebangsaan Berbasis NKRI Terhadap Pentingnya Manajemen Security di Era Digitalisasi - Edy Soesanto; Mahesa Agung; Vandra Firmansyah Sukma (Jurnal Manajemen Bisnis Digital Terkini, 2024)
The era of digitalization has brought significant changes in various aspects of life, including in security management. The wider application of digital technology requires an adaptive and innovative security approach to deal with evolving threats. In the context of the Unitary State of the Republic of Indonesia (NKRI), the implementation of national values in digital security management is very important. These values include unity, integrity, justice, democracy and diversity, which are the foundations of NKRI. This research aims to analyze the importance of security management in the digitalization era based on the NKRI's national values.The method used in this research is descriptive qualitative, with a literature study approach and document analysis related to digital security policies in Indonesia. The analysis focused on how NKRI national values are implemented in security management strategies and practices to face digital security challenges. The results show that the integration of national values in digital security management plays an important role in strengthening national resilience in the digital space. The implementation of national values helps in building a digital security system that is not only technically robust, but also responsive to Indonesia's social and cultural dynamics. This includes the development of inclusive cybersecurity policies, digital security education for diverse communities, and strengthening collaboration between sectors to strengthen the national digital security ecosystem.